THE ROLE OF MOBILE LEARNING APPLICATIONS IN ENHANCING LEXICAL PROFICIENCY IN MEDICAL EDUCATION ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
The study explores the impact of mobile learning applications on improving lexical proficiency in medical education. With the increasing use of smartphones and digital platforms in academic settings, mobile apps provide an innovative approach to mastering medical terminology. These applications offer interactive, accessible, and flexible learning experiences, aiding in vocabulary retention and comprehension. The research highlights the advantages of integrating mobile technologies into medical curricula, emphasizing the personalized, real-time feedback and on-the-go learning they offer. It also addresses potential challenges such as varying student engagement levels and technological limitations. Ultimately, the study underscores the need for further exploration into how these tools can be optimized for medical students’ diverse learning preferences and goals.